Use of Locking Compression Plate with or without Bone Grafting in Intra Articular and/or Highly Comminuted Distal End Radius Fractures: Our Experience in Adult Working Population in a Semi Urban Setup - Krishna, Mohan Sai; Taralekar, Gautam A; Rahate, Vaidyanath; Deshmukh, Aditya; Singh, Lokesh (Archives of Clinical and Biomedical Research, 2021)
Background and Objective: Incidence of fractures of distal radius are increasing due to more geriatric population and road traffic accidents and at the same time surgical treatment options for the same are modified continuously. The fundamental goal of treating distal radial fractures is restoration of normal or near normal alignment and articular congruity. Internal fixation using different plates can rigidly stabilize cancellous fragmented bone along with augmentation with bone graft which may not be amenable to k-wire or External fixation. Thus, this study was carried out in adult working population to study the functional outcome and effectiveness of operative management and study the complications of the same in a semi urban population. Method: This was a prospective observational study conducted in orthopaedic department of a tertiary center.30 patients with fractures of distal radius were included in the study on the basis of predefined inclusion and exclusion criteria. Patients were treated with open reduction and internal fixation with Locking Compression Plate through a volar approach and were followed up at 6 weeks, 3 months and with final assessment done at the end of 6 months post operatively and assessed clinically and radiologically. Result: The study comprised of 18 male and 12 female patients aged from 19 to 74 years with mean age of 47.1 years and more of left side involvement. Intra articular fractures (frykman type VIII and III) are most common. 29 (97%) cases had union within 3-4 months. Using the demerit scoring system of Gartland and Werley we had 50% excellent, 40% good, 10% fair and 0 poor results. Interpretation and Conclusion: In carefully selected patients even in the face of osteoporosis, fixation of fractures of distal end of radius with Locking Compression Plate along with bone grafting especially has satisfac